ECHOGRAPHY OF OVARIAN TUMOR FORMATIONS - Yangibaev Jonibek Saparbaevich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The most common reason for surgical intervention in women of reproductive age are functional ovarian cysts, although in most cases these formations disappear on their own within 3-6 months. The authors analyzed the frequency of this pathology, clinical features and diagnostics in girls of different age periods. Careful collection of anamnesis and correct assessment of not only the echographic characteristics of the ovarian cyst, but also the conformity of the structure and thickness of the endometrium to the phase of the menstrual cycle, in most cases helped to make the correct diagnosis and avoid unnecessary surgery. In the process of improving the methods of differential diagnosis of functional cysts and ovarian tumors, the proportion of operated patients decreased from 78 to 47%.